Model Sistem Pembelajaran dengan Pendekatan Case Method pada Mata Kuliah Akuntansi Keuangan Lanjutan - Riski Hernando (LPPM UBP, 2023)
The purpose of this study was to find out in depth the application of the learning system with a project based learning model with a case method approach in Advanced Financial Accounting courses in the Accounting Study Program, Faculty of Economics and Business, University of Jambi. The population in this study were fifth semester students of the Accounting Study Program, Faculty of Economics and Business, University of Jambi, with the research sample being all fifth semester students taking advanced financial accounting courses taught by researchers in 2022. The research approach uses qualitative studies by observing and observing in-depth student study results with a project based learning learning model with a case method approach. The results showed that the use of the project based learning model with the case method approach was able to increase student creativity and innovation in understanding the complex Advanced Financial Accounting course